Primeras evaluaciones del comportamiento del arandano alto (Vaccinium corymbosum L.) en Chile - Muñoz S, C.=700 1 Godoy A, I.; Lavin A, A.; Valenzuela B, J.
(En, Es)
Ilus., 12 ref.
Keywords: VACCINIUM CORYMBOSUM; ADAPTACION; ADAPTABILIDAD; CHILE; ARANDANO; AGRICULTURA TECNICA